Coherent tunnel repolarization of a hydrogen bonded chain - Tomchuk, P.M.; Luk’yanets, S.P. (Condensed Matter Physics, 1998)
In the present paper we suggest a possible mechanism of repolarization of
a short hydrogen bonded chain. This mechanism is based on the coherent
tunnel reorientation of ionic groups and is additional to the other one that
is realized due to the coherent tunnel repolarization of the hydrogen bonds
described in the previous work (J. Mol. Struct. 416, 161 (1997)). With the
aid of the instanton method the tunnelling frequency of this reorient transition
is calculated in the WKB approximation. The tunnelling frequency of
such a flip-flop process does not depend on temperature, and this effect
can be observed at low temperatures when tunnelling chain repolarization
prevails over the thermal activation one. В роботi запропоновано можливий механiзм переполяризацiї короткого ланцюжка водневих зв’язкiв. Цей механiзм базується на когерентнiй тунельнiй переорiєнтацiї йонних груп i є додатковим до механiзму когерентної тунельної переполяризацiї водневих зв’язкiв, який був дослiджений у попереднiй роботi (J.Mol.Struct. 416,161 (1997)). Частота цих тунельних переходiв була отримана в квазiкласичному
наближеннi, використовуючи iнстантонний метод. Такi осциляцiї можуть спостерiгатися при низьких температурах i їх частота не залежить вiд останньої, у випадку коли тунельнi процеси домiнують над
термiчно активованими процесами.